Improving Resuscitation Timing: Random Assignment of Interprofessional Team Leaders in Simulated Resuscitation. Issue 2 (27th February 2022) - Ambati, Shashikanth R.; Tamuz, Michal; DeVoe, Barbara; Rotjan, Andrew; Lesser, Martin; Gangadharan, Sandeep
Abstract : Objectives: The aims of the study were to assess whether preassigning a team leader influences resuscitation timing using simulation and to examine relationship between response timeliness and designated leader's profession, whether physician or nurse. Methods: This is a prospective study of intervention (leader assigned) and control (no assigned leader) teams of residents and nurses participating in a simulated scenario. The primary outcome was time to bag-valve-mask (BVM) ventilation. A secondary outcome measure compared difference in time to BVM between physician- and nurse-led teams. Results: We assessed 25 teams, leader assigned (n = 14) or control (n = 11), composed of 92 clinicians. Leaders emerged in most of the controls (10 of 11). The median time to BVM in the leader-assigned group was 41.5 seconds (interquartile range, 34–49 seconds) compared with 53 seconds (interquartile range, 27–85 seconds) for controls ( P = 0.13). In the leader-assigned group, 85% (12 of 14) of teams initiated BVM in less than 1 minute compared with only 54% teams (6 of 11) in controls ( P = 0.18). Among the leader-assigned teams, we randomly assigned residents to lead 8 teams and nurses to lead 6 teams. All the nurse-led teams (6 of 6) initiated BVM in less than 1 minute compared with fewer physician-led teams (6 of 8) and only approximately half of controls (6 of 11, P = 0.19). Conclusions: The leader-assigned teams and controls did not differ in resuscitation timeliness. Among leader-assigned teams, the differences in time to BVM between physician- and nurse-led teams were not statistically significant. However, all 6 nurse-led teams demonstrated timely resuscitation, suggesting a direction for future research on the feasibility of bedside nurses taking the lead during resuscitation, pending code team arrival.